SISTEM INFORMASI JADWAL SUNTIK KB BERBASIS DEKSTOP DENGAN SMS GATEWAY DI BPM DELIMA TAMPUBOLON - Rauf Fauzan; Mia Rahayu (Program Studi Sistem Informasi, Fakultas Teknik dan Ilmu Komputer, Universitas Komputer Indonesia., 2017)
BPM Delima Tamubolon is one of the health institutions located in Jl. Cisangkan, Padasuka Cimahi. BPM Delima Tampubolon itself is quite long in providing services to patients. The information system is used in BPM Delima Tampubolon still manual like in the process of providing injectables schedule frequent errors in the delivery schedule for injectables done by writing on the card acceptor and card check-up of patients. Therefore, it is necessary to have a Based Information Systems Computerized. The design of research using structured methods, methods development using Waterfall and tools used to design a system that Flow Map Document, Diagram Context,Diagram of Data Flow (DFD), Data Dictionary, Designing Database. While Based Information Systems selected Computerized Information System Injecting Schedule KB-Based SMS Gateway desktop by using the Java programming language and the MySQL database structure. With the System Information Schedule Injectable KB then expected BPM Delima Tampubolon can perform service activities program injectables better so that in the administration schedule of injectables, patient registration, examination of the patient, as well as report generation schedule injectables, become more leverage and guide other clinics.